Relevansi Budaya Keamanan Pangan dengan Implementasi Teknologi Industri 4.0 di Industri Pangan Indonesia - Bangun Raharjo; Winiati Pudji Rahayu; Dase Hunaefi (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2023)
The application of food safety culture (FSC) which is influenced by human behavior with the development of industrial technology (IT) 4.0 with less human resources provides a challenge to understand the relationship between them. The research objective was to provide quantitative data and suggestions for improving the implementation of the FSC dimensions in synergy with the progress of IT 4.0. This research involved 35 participants from 18 local companies and 17 multinational food companies (MFC/PMA) for the survey and invited 7 selected participants from both of them to join the FGD. The FSC survey showed that the gap organizational maturity in FSC implementation between local companies (2.93) and PMA (3.62) in Indonesia was 0.7 (world best practice 4.0 – 5.0). The three main benefits and opportunities for implementing IT 4.0 were effectiveness and efficiency, safe and quality products, and early detection to prevent non-conformities or product recalls. There were three main IT 4.0 application areas, namely production, quality, and engineering. The three main forms of IT 4.0 implementation were advanced robotics, big data, and internet of things (IoT). The FGD results showed the relevance between FSC and IT 4.0. Activities in IT 4.0 helped the food industry to manage food safety and quality management system better, because technical problems that previously took time and thought can be implemented effectively and efficiently. Data analysis can be carried out more in-depth, actual, and accurate. Further research is recommended to see the strength of the relationship between FSC and IT 4.0 parameters to determine critical areas with quantitative research methods and advanced statistical data processing.